700 EPICARDIAL ADIPOSE TISSUE AND ATRIAL FIBRILLATION, A REVIEW. (15th December 2022) - Cersosimo, Angelica; Bertuletti, Nicolò; Arabia, Gianmarco; Cerini, Manuel; Salghetti, Francesca; Milidoni, Antonino; Curnis, Antonio
Abstract: Aims: Atrial fibrillation (AF) is the most common cardiac arrhythmia closely associated with stroke, heart failure, and decreased quality of life. Excess adiposity has long been associated with increased cardiovascular disease and risk factor of AF. Methods: Epicardial Adipose Tissue (EAT) is the fat depot located between the myocardium and the epicardium supplied by branches of the coronary arteries. By contrast, pericardial adipose tissue (PAT) is located externally and is supplied by non-​coronary arteries. EAT fat thickness was first visualized by and measured with Transthoracic Two-dimensional (2D) Echocardiography because is visible as an echo free space between the outer wall of the myocardium and the visceral layer of the pericardium. Moreover, computed tomography (CT) has been used to measure EAT through accurate volumetric measurement. CMR imaging is instead considered the 'gold standard' modality for imaging adipose tissue.EAT function and morphology in normal conditions is protective but it function changes under pathological conditions.Lots of studies, infact, indicated higher pericardial fat volume was associated with a nearly 40% higher odds of prevalent AF, and the association remained significant even after adjustment for other AF risk factors including age, sex, myocardial infarction, heart failure, BMI, and other regional fat deposits. Infact, EAT volume is related to impaired diastolic function, elevated left ventricular mass, and enlarged left atrium. Moreover, a higher degree of EAT accumulation is often observed in patients with systematic inflammatory disease and oxidative stress, such as rheumatoid arthritis and psoriasis, compared with those without systematic inflammatory disease even after adjusting other risk factors. Free fatty acids can be transported from EAT to the myocardium and lead to electromechanical changes in atrial tissue: they separate cardiomyocytes and this situation result in conduction slowing, loss of side-​to-​side cell connections and myocardial disorganization that leads to conduction delay and re-​entry. Results: EAT is a modifiable cardiovascular risk factor and a potential novel therapeutic target owing to its responsiveness to drugs with pleiotropic effects such as GLP1R agonists (visceral fat reduction is one of the non-​glycaemic effects of the GLP1R agonists), SGLT2 inhibitors (reduction of intramyocardial lipid content by increasing EAT lipolysis and ketone body oxidation) and statins (reduction of EAT thickness through modulation of peroxisome proliferator-​activated receptors (PPARs)). Furthemore, suppression of AF after injecting botulinum toxin into EAT in patients with paroxysmal AF, both during postoperative cardiac surgery and catheter ablation of epicardial fat pad can also result in EAT reduction. Conclusion: EAT is a measurable and modifiable cardiovascular risk factor that adds qualitative value to the stratification of cardiovascular risk. In the context of atrial fibrillation, EAT represents a new pathogenic substrate through the regional secretion of factors that induce fibrosis and neurohormonal disarray of the atrial myocytes. Genetic studies are also optional to uncover pathophysiological mechanism of EAT-AF interaction and clarify causal relationship. Finally, more efforts should be made to realize application of EAT quantification in risk evaluation and management for AF.